Supplementation with a protein module in oncology patients - Apaza Duran, Alan Jimy (2022)
Cancer is the second leading cause of death in Latin America, and the economic cost it requires will increase markedly in future years (1). If nothing is done about it, cancer incidence and mortality in South and Central America will continue to rise sharply between 2012 and 2035 (2). It is expected that by 2030 the incidence of cancer will increase by 32%, reaching 5 million cases per year (1). At the level of Latin America, health policies have been implemented, where they prioritize the feeding of these patients to reduce the sequelae that the treatments can cause, obtaining optimal results (3). It is in this context that the effects of cancer and its treatment make it difficult to meet the nutritional requirements of patients. Chemotherapy is the most widely used medical treatment for cancer in the world. Knowing that cancer cells tend to grow and divide faster than normal cells, this is where chemotherapy has the greatest effect. However, the drugs administered cause cell damage as side effects (loss of appetite, nausea, vomiting, dry mouth, ulcers in the mouth or throat, changes in the taste of food, difficulty digesting, constipation, diarrhea, among others)